Effectiveness of bronchial thermoplasty for severe persistent bronchial asthma accompanied by Pseudomonas aeruginosa infection. (2022) - Ishii, Satoru; Iikura, Motoyasu; Sugiura, Yuriko; Matsuki, Rei; Izumi, Shinyu; Hojo, Masayuki; Sugiyama, Haruhito
Abstract: Bronchial thermoplasty (BT) is a type of bronchoscopic treatment specifically used for patients with severe asthma. Most severe asthmatics receive systemic steroids and are at risk of being immunocompromised. This raises the clinical question of whether or not BT can be effectively and safely performed in such patients. Herein, we report a case highlighting the effectiveness and safety of BT in a patient with severe persistent bronchial asthma and Pseudomonas aeruginosa infection . We performed BT on a 46-year-old woman undergoing treatment for severe persistent asthma with inhaled steroids and 20 mg prednisolone orally. Although she was deemed to be infection-free before the procedure, culture of endobronchial secretions obtained during the first BT procedure grew Pseudomonas aeruginosa . After the first BT, she was given clarithromycin 400 mg orally daily. The amount of sputum decreased with each BT session, and sputum culture for Pseudomonas aeruginosa turned negative by the third BT session. Respiratory function tests showed 23.7% improvement in % post-bronchodilator forced expiratory volume in 1.0 s (%FEV1.0 ) and the asthma quality of life questionnaire (AQLQ) score increased by 2.41 points after the third BT. Bronchial wall thickness decreased and infiltrative shadows on CT disappeared after the three BT sessions, along with decrease in the amount of purulent sputum. Improvement in her asthma symptoms, after three BT sessions allowed decrease in the prednisolone dose. We report the effectiveness of BT and infection control in a severe asthmatic with Pseudomonas aeruginosa infection. Highlights: Bronchial thermoplasty (BT) is a type of bronchoscopic treatment specifically used for patients with severe asthma. There is a clinical question that whether we can perform the BT effectively and safely on immunocompromised patients. We report the effectiveness of BT and infection control in a severe asthmatic with Pseudomonas aeruginosa infection.